Estudo comparativo de adversativas no português e no catalão dos sécs. XII a XVI - Danivia da Cunha Mattozo (2008)
This research went through the historical track of the Portuguese negative conjunctions mas, però and porem and the Catalan negative conjunctions mes and però, both from the XIII to the XVI centuries. In chapter 1, it was presented the history of both the Portuguese and the Catalan negative conjunctions. In this first part, the negativeness concept was analyzed through the study of traditional grammars. Later on, a brief review of the Portuguese negative conjunctions mas, però and porem and the Catalans mes and però was made, retaking their track from Latin to archaic Portuguese and Catalan. At this moment, it is listed the main processes by which they went through and the hypotheses that there are in the literature to explain them. In chapter 2, this research goals and methods are presented. In this chapter it is presented both the Portuguese and Catalan corpus, the way the data is collected, and the analysis proposal. The chapter 3 was reserved to the data description. The organized data are presented in a way that one is able to make a qualitative and quantitative analysis. In this analysis, the following aspects were observed: frequency; semantic values; syntactic joints level; syntactic position; sentence type and negative element accompaniment. In chapter 4, the pre-established hypotheses were reviewed, basing in results obtained by the data description, new considerations relationed with syntax aspects were proposed, comparation between Portuguese and Catalan items was made and new possible investigations were pointed. Finally, at the conclusion, the research results about the items mas, però and porém from the Portuguese and mes and però from the Catalan were reviewed.